Vegetation management intensity and landscape diversity alter plant species richness, functional traits and community composition across European vineyards. (January 2020) - Hall, Rea M.; Penke, Nicole; Kriechbaum, Monika; Kratschmer, Sophie; Jung, Vincent; Chollet, Simon; Guernion, Muriel; Nicolai, Annegret; Burel, Francoise; Fertil, Albin; Lora, Ángel; Sánchez-Cuesta, Rafael; et al.
Highlights: Bare soil management reduced dissimilarity of plant traits and species richness. Vegetation cover and biodiversity benefit from low disturbance frequencies. Vegetation management needs to deal with trade-offs: Species-poor grass cover crops reduce species richness and functional divergence. However, cover crops increased vegetation cover thereby reducing soil erosion risk. Landscape diversity had only a slight positive impact on plant species richness. Abstract: Land-use intensification at the field and landscape scale is a strong driver for declining biodiversity and ecosystem service provision. Vineyards are characterised by non-productive inter-rows, which could potentially host diverse plant communities. Mulching, tillage or herbicides are used to mitigate the competition between vines and the inter-row vegetation. As plant species with the same set of functional traits will respond similarly to environmental filters like management measures, knowledge about plant trait–environment-relations can be used to predict community and ecosystem processes which are essential for preserving ecosystem services like soil erosion mitigation. We hypothesized that higher vegetation management intensity reduces plant (functional) diversity, changes functional traits and community composition. Across Europe, four viticultural regions in Austria, France, Spain and Romania, which comprised 78 vineyards differing in vegetation management intensity (bare soil, temporary and permanent vegetation cover), were selected for sampling vascular plant diversity. Around each vineyard, the surrounding landscape composition and landscape diversity was investigated within a 750 m radius. Rao's quadratic entropy as a measure of functional diversity was calculated based on a selection of plant functional traits. The effects of management and landscape variables on species richness, functional traits, functional diversity and vegetation cover were analysed by generalized linear mixed models and random forests (RF). Furthermore, plant community composition was analysed with non-metric multidimensional scaling (NMDS). Higher management intensities resulted in lower species richness, functional diversity and vegetation cover. The country with the related divergent edaphoclimatic conditions was a significant factor affecting most diversity and functional trait parameters, whereas landscape diversity increased plant species richness only slightly. Vegetation management intensity had the highest explanatory power for species richness, functional diversity and most functional traits according to RF analysis. Consequently, plant functional traits like a higher coverage of ruderals and annuals could be clearly related to bare soil management. Furthermore, the type of cover crops influenced the relationship between annual and perennial plant species, Grime plant strategy types and species diversity. Accordingly, NMDS showed a separation between permanent vegetation cover and bare soil vineyards. The overall positive effect of extensive management and the use of diverse cover crops or spontaneous vegetation in vineyard inter-rows should be better implemented in agricultural policies to support both, biodiversity and ecosystem provision.